Sensitivity and Noise Analysis of Resonant All-Fiber Optic Current Transformers - Zhiguo Jiang; Lixi Zhang; Guozhong Wang; Lijun Jin (IEEE Photonics Journal)
The sensitivity and noise of an all-fiber optic current transformer (AFOCT) scheme named resonant AFOCT are analyzed, which senses the current information by measuring the frequency difference between clockwise and counterclockwise resonances inside a fiber ring resonator (FRR). Compared with polarization-type and interference-type AFOCT, the sensitivity of the resonant AFOCT can be improved by increasing the finesse of the FRR. The mathematical model of the resonant AFOCT is established, and the sensitivity expression of the resonant AFOCT limited by the sensitivity of the photodetector is derived. For the small current measurement of 1 mA level, the carrier suppression level of phase modulation is required to be better than ${{ρ }_{\text{ccw}}}{{ρ }_{\text{cw}}}{\rm{ = }} - \mathrm{110 \, dB}$ , and the intensity of unwanted polarization eigenstate of the FRR should be suppressed to less than −68 dBm. The non-ideal characteristics of fiber quarter-waveplate and the residual linear birefringence of spun fiber mainly affect the scale factor of the resonant AFOCT. The resonant AFOCT will be an important way to achieve high-precision of the current transformer.